ENGINEERING METHOD FOR CALCULATING STEEL-REINFORCED CONCRETE ELEMENTS WITH FLEXIBILITY (Academic journal Industrial Machine Building Civil Engineering, 2019)
In the article presents an engineering method for calculating compressed flexible reinforced concrete elements with sheet reinforcement over a steel cross section. The results of the calculation are compared with the experimental data. Calculation ofload-bearing capacity of reinforced concrete flexible elements with sheet reinforcement is based on the method of boundarystates. The work of specimens under load and the nature of the load-bearing capacity depending on the height and eccentricity of the effort were investigated. The proposed method of calculating compressed elements with sheet reinforcement on asteel-cross-section allows to take into account their flexibility in both axial and out-of-center application of load.
Keywords: steel reinforced concrete; bearing capacity; sheet reinforcement; eccentricity; flexibility